A audiodescrição, os textos alternativos e as tecnologias da comunicação e informação: Um estudo a cerca da escolarização das pessoas com deficiência visual - Fernandes, Heverton Rodrigues (2023)
Much has been said about the use of information and communication technology (ICT) in the process of teaching and learning of the so-called digital natives. ICT comprises pieces of technology that allow the creation, storage, processing and sharing of information. In addition to informing, amusing and entertaining, these tools can be a may help students in their schooling process. However, the use of ICT in the schooling of visually impaired people is rarely discussed. One of the main barriers visually impaired people face in the use of ICT in the teaching and learning process is the lack of audio description or alternative texts of the contents. The aim of this research was to investigate how ICT is adopted in the schooling of visually impaired students at elementary schools and how audio description resources and alternative texts are applied to the process. Particularly, we seek to identify which digital technology has been adopted in teaching visually impaired students and how audio description resources and alternative texts have been used. We also sought to analyze teachers’ perception regarding the use of ICT, audio description resources, and alternative texts in teaching strategies. In order to achieve the objectives of this study, a qualitative research and Content Analysis were carried out to collect data through questionnaires applied to teachers at local elementary schools. On the one hand, the results showed that ICT in classroom is highly valued, with different uses as accessibility resource for visually impaired students. ICT is being used by teachers as a means of benefiting the student and enhancing students' teaching and learning methods. On the other hand, data analysis showed that teachers do not know the most up-to-date and functional accessibility tools and resources, such as audio description and alternative texts, which could be applied to the teaching practice, in order to enhance learning in the schooling processes of visually impaired people.